How does nonsyndromic craniosynostosis affect on bone width of nasal cavity in children? – Computed tomography study - Gruszczyńska, Katarzyna (PLoS One, 2018)
Craniosynostosis is caused by premature fusion of one or more cranial sutures, restricting skull, brain and face growth. Nonsyndromic craniosynostosis could disturb the proportions of face. Although morphometric diameters of nasal cavity in healthy children are already known, they have not been established yet in children with nonsyndromic craniosynostosis. The aim our study was to check whether diameters of bone structures of nasal cavity in children with nonsyndromic craniosynostosis measured in CT are within normal range. 249 children aged 0–36 months (96 with clinical diagnosis of nonsyndromic craniosynostosis and 153 in control group) were included into the study. The following diameters were measured on head CT scans: anterior bony width (ABW), bony choanal aperture width (BCAW), right and left posterior bony width (between bone sidewall and nasal cavity septum—RPBW and LPBW). The study group has been divided into 4 categories, depending on child’s age. The dimensions measured between bone structures of nasal cavity were statistically significantly lower in comparison to the control group. They did not depend on the sex for ABW, nor on age in groups 7–12 months and < 2 years for BCAW, RPBW and LPBW. The measured dimensions increased with age. In children with nonsyndromic craniosynostosis the diameter of pyriform aperture and bony choanal aperture were lower than in controls, what may be described as fronto-orbital anomalies. Morphometric measurements of anthropometric indicators on CT scans could be used as standards in the clinical identification of craniosynostosis type and may help in planning surgical procedures, particularly in the facial skeleton in children.